2018
DOI: 10.1007/s00436-018-6062-9
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships within Dicrocoeliidae (Platyhelminthes: Digenea) from birds from the Czech Republic using partial 28S rDNA sequences

Abstract: Partial (D1-D3) 28S rRNA gene sequences from 16 isolates of digenean parasites of the family Dicrocoeliidae recovered from 16 bird species from the Czech Republic were used for phylogenetic reconstruction. Comparison with sequences available from GenBank suggests that the genus Brachylecithum is paraphyletic, requiring further validation and possible systematic revision. Although partial 28S rDNA is relatively conserved, analyses suggest that the following taxa are synonymous: Lutztrema attenuatum = L. monente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
(18 reference statements)
1
15
2
Order By: Relevance
“…and Brachylecithum sp. was consistent with their respective placement in the present as well as in previous phylogenetic analyses based on 28S rDNA sequences [1,15]. The tree also showed that the family Paragonimidae (represented by Paragonimus spp.)…”
Section: Phylogeny Of the Dicrocoeliidae Based On Mt Genome Sequencessupporting
confidence: 91%
See 4 more Smart Citations
“…and Brachylecithum sp. was consistent with their respective placement in the present as well as in previous phylogenetic analyses based on 28S rDNA sequences [1,15]. The tree also showed that the family Paragonimidae (represented by Paragonimus spp.)…”
Section: Phylogeny Of the Dicrocoeliidae Based On Mt Genome Sequencessupporting
confidence: 91%
“…An approximately 1300 bp long fragment at the 5′-end of the 28S gene of three avian dicrocoeliid species was amplified, as described in previous studies [1,15] using the primers LSU5 and 1500R [12,25] with an annealing temperature of 55 °C. For L. longicauda, DNA of two specimens (one from each host species) was used for the amplification of 28S gene in order to ensure that different isolates of the same species are identical.…”
Section: Amplification and Analysis Of Nuclear 28s Rdnamentioning
confidence: 99%
See 3 more Smart Citations